A novel approach for preparation and in situ tensile testing of silica glass membranes in the TEM - Mackovic, Mirza; Przybilla, Thomas; Dieker, Christel; Herre, Patrick; Romeis, Stefan; Stara, Hana; Schrenker, Nadine; Peukert, Wolfgang; Spiecker, Erdmann (Frontiers in Materials, 2017)
The mechanical behavior of glasses in the micro- and/or nanometer regime increasingly gains importance in nowadays modern technology. However, suitable small scale preparation and mechanical testing approaches for a reliable assessment of the mechanical properties of glasses still remain a big challenge. In the present work, a novel approach for site-specific preparation and quantitative in situ tensile testing of thin silica glass membranes in the transmission electron microscope is presented. Thereby, advanced focused ion beam techniques are used for the preparation of nanoscale dog bone shaped silica glass specimens suitable for in situ tensile testing. Small amounts of gallium are detected on the surface of the membranes resulting from redeposition effects during the focused ion beam preparation procedure. Possible structural changes of silica glass upon irradiation with electrons and gallium ions are investigated by controlled irradiation experiments, followed by a structural analysis using Raman spectroscopy. While moderate electron beam irradiation does not alter the structure of silica glass, ion beam irradiation results in minor densification of the silica glass membranes. In situ tensile testing of membranes under electron beam irradiation results in distinctive elongations without fracture confirming the phenomenon of superplasticity. In contrast, in situ tensile testing in the absence of the electron beam reveals an elastic/plastic deformation behavior, and finally leads to fracture of the membranes. The Young’s moduli of the glass membranes pulled at beam off conditions in the TEM are comparable with values known for bulk fused silica, while the tensile strength is in the range of values reported for silica glass fibers with comparable dimensions. The impact of electron beam irradiation on the mechanical properties of silica glass membranes is further discussed. The results of the present work open new avenues for dedicated preparation and nanomechanical characterization of silica glasses, and further contribute to a fundamental understanding of the mechanical behavior of such glasses when being scaled down to the nanometer regim
Keywords: Silica glass; in situ TEM; in situ nanomechanical testing; Mechanical Properties; Electron beam irradiation; superplasticity; FIB; Raman spectroscopy

Coexistence of both gyroid chiralities in individual butterfly wing scales of Callophrys rubi - Winter, Benjamin; Butz, Benjamin; Dieker, Christel; Schroeder-Turk, Gerd E.; Mecke, Klaus; Spiecker, Erdmann (Proceedings of the National Academy of Sciences of the United States of America, 2015)
The wing scales of the Green Hairstreak butterfly Callophrys rubi consist of crystalline domains with sizes of a few micrometers, which exhibit a congenitally handed porous chitin microstructure identified as the chiral triply periodic single-gyroid structure. Here, the chirality and crystallographic texture of these domains are investigated by means of electron tomography. The tomograms unambiguously reveal the coexistence of the two enantiomeric forms of opposite handedness: the left- and right-handed gyroids. These two enantiomers appear with nonequal probabilities, implying that molecularly chiral constituents of the biological formation process presumably invoke a chiral symmetry break, resulting in a preferred enantiomeric form of the gyroid structure. Assuming validity of the formation model proposed by Ghiradella H (1989) J Morphol 202(1): 69-88 and Saranathan V, et al. (2010) Proc Natl Acad Sci USA 107(26): 11676-11681, where the two enantiomeric labyrinthine domains of the gyroid are connected to the extracellular and intra-SER spaces, our findings imply that the structural chirality of the single gyroid is, however, not caused by the molecular chirality of chitin. Furthermore, the wing scales are found to be highly textured, with a substantial fraction of domains exhibiting the < 001 > directions of the gyroid crystal aligned parallel to the scale surface normal. Both findings are needed to completely understand the photonic purpose of the single gyroid in gyroid-forming butterflies. More importantly, they show the level of control that morphogenesis exerts over secondary features of biological nanostructures, such as chirality or crystallographic texture, providing inspiration for biomimetic replication strategies for synthetic self-assembly mechanisms.
Keywords: electron tomography; chirality; crystallographic texture; photonic crystal; butterfly wing scales

Controlling morphology and optical properties of self-catalyzed, mask-free GaN rods and nanorods by metal-organic vapor phase epitaxy - Tessarek, C.; Bashouti, M.; Heilmann, M.; Dieker, Christel; Knoke, Isabel; Spiecker, Erdmann; Christiansen, S. (Journal of Applied Physics, 2013)
A simple self-catalyzed and mask-free approach will be presented to grow GaN rods and nanorods based on the metal-organic vapor phase epitaxy technique. The growth parameter dependent adjustment of the morphology of the structures will be discussed. Rods and nanorods with diameters reaching from a few mu m down to 100 nm, heights up to 48 mu m, and densities up to 8.10(7) cm(-2) are all vertically aligned with respect to the sample surface and exhibiting a hexagonal shape with smooth sidewall facets. Optical properties of GaN nanorods were determined using cathodoluminescence. It will be shown that the optical properties can be improved just by reducing the Ga precursor flow. Furthermore, for regular hexagonal shaped rods and nanorods, whispering gallery modes with quality factors up to 500 were observed by cathodoluminescence pointing out high morphological quality of the structures. Structural investigations using transmission electron microscopy show that larger GaN nanorods (diameter > 500 nm) contain threading dislocations in the bottom part and vertical inversion domain boundaries, which separate a Ga-polar core from a N-polar shell. In contrast, small GaN nanorods (similar to 200 nm) are largely free of such extended defects. Finally, evidence for a self-catalyzed, Ga-induced vapor-liquid-solid growth will be discussed. (C) 2013 AIP Publishing LLC.

Fully Patterned Low-Voltage Transparent Metal Oxide Transistors Deposited Solely by Chemical Spray Pyrolysis - Faber, Hendrik; Butz, Benjamin; Dieker, Christel; Spiecker, Erdmann; Halik, Marcus (Advanced Functional Materials, 2013)
All-inorganic transparent thin-film transistors deposited solely by the solution processing method of spray pyrolysis are reported. Different precursor materials are employed to create conducting and semiconducting species of ZnO acting as electrodes and active channel material, respectively, as well as zirconium oxide as gate dielectric layer. Additionally, a simple stencil mask system provides sufficient resolution to realize the necessary geometric patterns. As a result, fully functional low-voltage n-type transistors with a mobility of 0.18 cm2 V−1 s−1 can be demonstrated via a technique that bears the potential for upscaling. A detailed microscopic evaluation of the channel region by electron diffraction, high-resolution and analytical TEM confirms the layer stacking and provides detailed information on the chemical composition and nanocrystalline nature of the individual layers.

Germanium Template Assisted Integration of Gallium Arsenide Nanocrystals on Silicon: A Versatile Platform for Modern Optoelectronic Materials - Schmitt, Sebastian W.; Sarau, George; Speich, Claudia; Doehler, Gottfried H.; Liu, Ziheng; Hao, Xiaojing; Rechberger, Stefanie; Dieker, Christel; Spiecker, Erdmann; Prost, Werner; Tegude, Franz-Josef; Conibeer, Gavin; et al. (Advanced Optical Materials, 2018)
Metal organic vapor phase epitaxy is used to grow gallium arsenide (GaAs) nanocrystals (NCs) on germanium (Ge) templates on nanoscopic silicon (Si) threads prepared by reactive ion etching. Scanning transmission electron microscopy with energy dispersive X-ray measurements shows an epitaxial growth of the GaAs on the Ge template that is supported by the Si thread, and that Ge doping is induced to the GaAs by the template. On Ge templates of about 60 nm diameter, as-grown GaAs NCs show a very regular rhombic- dodecahedral outer shape that can be explained by a preferential growth along the <110> plane. Photoluminescence measurements of the Ge/GaAs structures reveal radiative emission peaks on top of the GaAs band-to-band emission and at sub-band gap energies. While high energy peaks are originating from Ge acceptor levels in GaAs, sub-band gap peaks can be explained by radiation from Ge donor and acceptor bands that are ampliﬁed by photonic modes hosted in the rhombic- dodecahedral GaAs NCs. This study shows that a template-assisted crystal growth at the nanoscale opens up routes for a versatile integration of strongly emitting nanomaterials for a use in on-chip solid state lighting and photonics.
Keywords: Gallium arsenide; Germanium; Nanocrystals; Photoluminescence; Photonics

Growth of GaN Nanorods and Wires and Spectral Tuning of Whispering Gallery Modes in Tapered GaN Wires - Tessarek, Christian; Dieker, Christel; Spiecker, Erdmann; Christiansen, Silke (Japanese Journal of Applied Physics, 2013)
This paper reports on the growth of GaN nanorods and wires by metal-organic vapor phase epitaxy. Density, height and diameter are strongly influenced by the growth time. A deposition time of a few minutes leads to the formation of GaN nanorods. Increasing the deposition time up to 1 h yields wires with heights exceeding 47 mu m. Transmission electron microscopy and convergent beam electron diffraction measurements are showing the presence of N- and Ga-polar GaN in a single nanorod. Cathodoluminescence measurements are performed showing the appearance of whispering gallery modes. Due to slight tapering of the wires the whispering gallery modes can be spectrally tuned by changing the position of the exposing electron beam at the sidewall facet of the rod. (C) 2013 The Japan Society of Applied Physics

Nanowire Arrays in Multicrystalline Silicon Thin Films on Glass: A Promising Material for Research and Applications in Nanotechnology - Schmitt, Sebastian W.; Schechtel, Florian; Amkreutz, Daniel; Bashouti, Muhammad; Srivastava, Sanjay K.; Hoffmann, Bjoern; Dieker, Christel; Spiecker, Erdmann; Rech, Bernd; Christiansen, Silke H. (Nano Letters, 2012)
Silicon nanowires (SiNW) were formed on large grained, electron-beam crystallized silicon (Si) thin films of only 6 pm thickness on glass using nanosphere lithography (NSL) in combination with reactive ion etching (RIE). Electron backscatter diffraction (EBSD) and transmission electron microscopy (TEM) studies revealed outstanding structural properties of this nanomaterial. It could be shown that SiNWs with entirely predetermined shapes including lengths, diameters and spacings and straight side walls form independently of their crystalline orientation and arrange in ordered arrays on glass. Furthermore, for the first time grain boundaries could be observed in individual, straightly etched SiNWs. After heat treatment an electronic grade surface quality of the SiNWs could be shown by X-ray photoelectron spectroscopy (XPS). Integrating sphere measurements show that SiNW patterning of the multicrystalline Si (mc-Si) starting thin film on glass substantially increases absorption and reduces reflection, as being desired for an application in thin film photovoltaics (PV). The multicrystalline SiNWs directly mark a starting point for research not only in PV but also in other areas like nanoelectronics, surface functionalization, and nanomechanics.
Keywords: Silicon nanowires; multicrystalline; silicon thin film on glass; e-beam crystallization; photovoltaics; absorption; reactive ion etching; EBSD; TEM; XPS

New insights into colloidal gold flakes: structural investigation, micro-ellipsometry and thinning procedure towards ultrathin monocrystalline layers - Hoffmann, B.; Bashouti, M. Y.; Feichtner, Thorsten; Mackovic, Mirza; Dieker, Christel; Salaheldin, A. M.; Richter, P.; Gordan, O. D.; Zahn, D. R. T.; Spiecker, Erdmann; Christiansen, S.; Hoffmann, Björn (Nanoscale, 2016)
High-quality fabrication of plasmonic devices often relies on wet-chemically grown ultraflat, presumably single-crystalline gold flakes due to their superior materials properties. However, important details about their intrinsic structure and their optical properties are not well understood yet. In this study, we present a synthesis routine for large flakes with diameters of up to 70 mu m and an in-depth investigation of their structural and optical properties. The flakes are precisely analyzed by transmission electron microscopy, electron backscatter diffraction and micro-ellipsometry. We found new evidence for the existence of twins extending parallel to the Au flake 111 surfaces which have been found to not interfere with the presented nanopatterning. Micro-Ellipsometry was carried out to determine the complex dielectric function and to compare it to previous measurements of bulk single crystalline gold. Finally, we used focused ion beam milling to prepare smooth crystalline layers and high-quality nanostructures with desired thickness down to 10 nm to demonstrate the outstanding properties of the flakes. Our findings support the plasmonics and nano optics community with a better understanding of this material which is ideally suited for superior plasmonic nanostructures.

Optical properties of vertical, tilted and in-plane GaN nanowires on different crystallographic orientations of sapphire - Tessarek, C.; Figge, S.; Gust, Arne; Heilmann, M.; Dieker, Christel; Spiecker, Erdmann; Christiansen, S. (Journal of Physics D-Applied Physics, 2014)
Self-catalysed and self-organized GaN nanowires were grown on c-, a-, m- and r-plane sapphire by metal-organic vapour phase epitaxy. In dependence on the crystallographic orientation of the sapphire substrate, vertical, tilted and in-plane GaN nanowires were achieved. The nanowire orientation is visualized by scanning electron microscopy and analysed by x-ray diffraction. The influence of the sapphire nitridation step on the nanowire formation is investigated. Spatially and spectrally resolved cathodoluminescence studies are carried out on the GaN nanowires to analyse the influence of the GaN nanowire orientation as well as the presence of both N- and Ga-polar sections in a single nanowire on the optical properties.
Keywords: GaN; nanowires; sapphire; growth; MOVPE; cathodoluminescence

Self-Catalyzed Growth of Vertically Aligned InN Nanorods by Metal-Organic Vapor Phase Epitaxy - Tessarek, C.; Fladischer, Stefanie; Dieker, Christel; Sarau, G.; Hoffmann, Björn; Bashouti, M.; Goebelt, M.; Heilmann, M.; Latzel, Michael; Butzen, E.; Figge, S.; Gust, A.; et al. (Nano Letters, 2016)
Vertically aligned hexagonal InN nanorods were grown mask-free by conventional metal organic vapor phase epitaxy without any foreign catalyst. The In droplets on top of the nanorod's indicate a self-catalytic vapor liquid solid growth mode. A systematic study on important growth parameters has been carried out for the optimization of nanorod morphology. The nanorod N-polarity, induced by high temperature nitridation of the sapphire substrate, IS necessary to achieve vertical growth. Hydrogen, usually inapplicable during InN growth due to formation of metallic indium, and silane are needed to enhance the aspect ratio and to reduce parasitic deposition beside the nanorods on the sapphire surface. The results reveal many similarities between InN and GaN nanorod growth showing that the process despite the large difference in growth temperature is similar. Transmission electron microscopy, spatially resolved energy-dispersive X-ray spectroscopy, X-ray diffraction, X-ray photoelectron spectroscopy, and Raman spectroscopy have been performed to analyze the structural properties. Spatially resolved cathodoluminescence investigations are carried out to verify the optical activity of the InN nanorods. The InN nanorods are expected to be the material of choice for high-efficiency hot carrier solar cells.
Keywords: InN; nanorods; MOVPE; growth; vapor-liquid-solid; cathodoluminescence

The Role of Si during the Growth of GaN Micro- and Nanorods - Tessarek, C.; Heilmann, M.; Butzen, E.; Haab, A.; Hardtdegen, Hilde; Dieker, Christel; Spiecker, Erdmann; Christiansen, S. (Crystal Growth & Design, 2014)
The role of Si during the metal-organic vapor phase epitaxy of GaN rods is investigated. Already a small amount of Si strongly enhances the vertical growth of GaN. Reactive ion etching experiments show that the inner volume of the rod is much more strongly etched than the m-plane surface layer. Transmission electron microscopy and energy dispersive X-ray spectroscopy measurements reveal that Si is predominiantly incorporated in the surface layer of the m-plane sidewall facets of the rods. The formation of a SiN layer prevents growth on and etching of the m-planes and enhances the mobility of atoms promoting vertical growth. Annealing experiments demonstrate the extraordinary thermal resistivity in comparison to undoped GaN rod structures and GaN layers. The subsequent InGaN quantum well growth on the GaN rods reveals the antisurfactant effect of the SiN layer. A model based on the vapor-liquid-solid growth mode is proposed. The results help to understand the role of Si during growth of GaN rod structures to improve the performance of rod based light emitting and electronic devices.

Understanding GaN/InGaN core-shell growth towards high quality factor whispering gallery modes from non-polar InGaN quantum wells on GaN rods. - Tessarek, Christian; Rechberger, Stefanie; Dieker, Christel; Heilmann, Martin; Spiecker, Erdmann; Christiansen, S. H. (Nanotechnology, 2017)
GaN microrods are used as a basis for subsequent InGaN quantum well (QW) and quantum dot deposition by metal-organic vapor phase epitaxy. The coverage of the shell along the sidewall of rods is dependent on the rod growth time and a complete coverage is obtained for shorter rod growth times. Transmission electron microscopy measurements are performed to reveal the structural properties of the InGaN layer on the sidewall facet and on the top facet. The presence of layers in the microrod and on the microrod surface will be discussed with respect to GaN and InGaN growth. A detailed model will be presented explaining the formation of multiple SiN layers and the partial and full coverage of the shell around the core. Cathodoluminescence measurements are performed to analyze the InGaN emission properties along the microrod and to study the microresonator properties of such hexagonal core-shell structures. High quality factor whispering gallery modes with [Formula: see text] are reported for the first time in a GaN microrod/InGaN non-polar QW core-shell geometry. The GaN/InGaN core-shell microrods are expected to be promising building blocks for low-threshold laser diodes and ultra-sensitive optical sensors.
Keywords: GaN; InGaN; SiN; rods; core–shell; quantum wells; whispering gallery modes